BEYOND SYNTACTIC DELETION: A COGNITIVE SEMANTIC ACCOUNT OF ELLIPSIS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Ellipsis — the omission of linguistic material recoverable from context — has been studied predominantly within generative syntactic frameworks that treat it as a deletion or non-pronunciation operation applying to fully formed syntactic structures. This article proposes a complementary, usage-based account grounded in cognitive semantics and construction grammar. Drawing on naturally occurring data from English conversational and written discourse, we argue that ellipsis resolution is primarily a conceptual rather than a formal syntactic process: interlocutors reconstruct omitted material through frame activation, mental-space mapping, and prototype-based categorisation rather than by reversing covert syntactic deletions. We report findings from a corpus-based analysis of 1,200 elliptical utterances spanning verb-phrase ellipsis (VPE), nominal ellipsis (NE), and sluicing, demonstrating that antecedent-recovery rates and interpretation accuracy correlate more strongly with conceptual salience measures than with structural parallelism indices. The implications for theories of language comprehension, discourse coherence, and the syntax–semantics interface are discussed.
Keywords: ellipsis; cognitive semantics; construction grammar; mental spaces; discourse coherence; verb-phrase ellipsis; sluicing